Investigation of writing error in staggered heated-dot magnetic recording systems - W. Tipcharoen; C. Warisarn; D. Tongsomporn; D. Karns; P. Kovintavewat (My University, 2017)
To achieve an ultra-high storage capacity, heated-dot magnetic recording (HDMR) has been proposed, which heats a bit-patterned medium before recording data. Generally, an error during the HDMR writing process comes from several sources; however, we only investigate the effects of staggered island arrangement, island size fluctuation caused by imperfect fabrication, and main pole position fluctuation. Simulation results demonstrate that a writing error can be minimized by using a staggered array (hexagonal lattice) instead of a square array. Under the effect of main pole position fluctuation, the writing error is higher than the system without main pole position fluctuation. Finally, we found that the error percentage can drop below 10% when the island size is 8.5 nm and the standard deviation of the island size is 1 nm in the absence of main pole jitter.
Keywords: Position (finance); Position error; Magnetic properties of thin films